Hak dan Kewajiban Suami Istri Akibat Putusan Mahkamah Konstitusi tentang Pembuatan Perjanjian Perkawinan Setelah Perkawinan Berlangsung - Muhamad Lufti Juniarto Ahmad (University of Jember, 2018)
The Constitutional Court has issued a decision number 69/PUU-XIII/2015 in dealing with rights and duties between husband and wife under a marriage agreement of treasure separation. As a result of such constitutional decision, however, there should not be provisions that harm third parties, creditor as an instance, when debts have prevailed during the marriage term. As a means to protect creditor, it should refer to Article 31 paragraph 1 of Marriage Act (UUP) in which both husband and wife are equal. With regard to repayment of joint debts, both should remain equal in dealing with rights and duties in which repayment is collected from joint treasure. While it is not sufficient, it is collected from husband’s treasure and if it is still not sufficient, it is collected from wife’s treasure respectively as it is mentioned in Articles 33 and 34 paragraph 1 Marriage Act. Keywords: Rights and Duties, Marriage, Constitutional Court’s Decision